Estudio de factibilidad para la creación de la empresa “Los Arias" productora y comercializadora de artes manuales en la ciudad de Armenia, Quindío, para exportar a Alemania, Francia y Reino Unido (2013)
This work tries demonstrate step by step the creation, implementation, search and consolidation of international markets for the product towels in cotton with the added value of a craft, cross stitch, entirely by hand, looking always ensure maximum quality. The product aims to export not only employment at the personal use, also like decoration item that can be purchased for gifts or own use. The company THE ARIAS, is a company that was born into a family, when one of the members, "THE GRANDMA" decided to devote his life to the craft and pass that knowledge on to her children, so that they in turn were refined and passed from generation to generation, including those new knowledge that they gained from the way, to become today a compilation of all these skills and abilities represented in crafts. This project takes as its single biggest art embroidery cross stitch, which is added to a cotton towel, resulting in a unique and different product. By using different tools to determine which countries will export the product and made the search and selection of the information through websites specializing in foreign trade.